Dynamic Responses of Long-Span Steel Truss Girder Cable-Stayed Bridge With a Single Pylon - Yong Zeng; Jiahao Wei; Yutong Zeng; Yunchuan Xiao; Hongwei Mao; Ming Huang; Zhongfu Xiang; Jianting Zhou (Advances in Civil Engineering)
The study investigates the seismic response of long-span single-tower and single-cable steel truss girder cable-stayed bridges, which structurally differ from traditional bridge types, and there is limited research on the influence of cable arrangement on the seismic response of long-span single-tower steel truss girder cable-stayed bridges. Therefore, based on the engineering background of the world’s largest span single-tower and single-cable steel truss girder cable-stayed bridge, a finite element model of the entire bridge is established to study the effect of cable arrangement on the seismic response of the bridge. The results indicate that although a double-cable plane arrangement can slightly reduce the torsion of the main girder, it cannot completely eliminate the occurrence of torsional vibration modes. However, by employing structural measures such as sufficient stiffness and reasonable width of the steel truss girder, the negative impact of single-cable plane arrangement on the dynamic characteristics of the bridge can be mitigated. It is suggested to adopt a single-cable plane arrangement when the standard width of the main girder is narrow, while a double-cable plane arrangement is more suitable when the standard width of the main girder is wide. These findings provide an important reference for the design of similar structures in the future.